Food choice by people with intellectual disabilities at day centres: A qualitative study. (June 2015) - Cartwright, Luke; Reid, Marie; Hammersley, Richard; Blackburn, Chrissie; Glover, Lesley
People with intellectual disabilities experience a range of health inequalities. It is important to investigate possible contributory factors that may lead to these inequalities. This qualitative study identified some difficulties for healthy eating in day centres. (1) Service users and their family carers were aware of healthy food choices but framed these as diets for weight loss rather than as everyday eating. (2) Paid carers and managers regarded the principle of service user autonomy and choice as paramount, which meant that they felt limited in their capacity to influence food choices, which they attributed to the home environment. (3) Carers used food as a treat, a reward and for social bonding with service users. (4) Service users' food choices modelled other service users' and carers' choices at the time. It is suggested that healthy eating should be made more of a priority in day care, with a view to promoting exemplarily behaviour that might influence food choice at home.